Effects of Working Couple's Retirement Sequence on Satisfaction in Patriarchal Culture Country: Probing on Gender Difference. (October 2018) - Lee, Ayoung; Cho, Joonmo
We examined the effects of the differences in the retirement sequence (i.e., who retires first between spouses) on satisfaction in Korea of patriarchal culture. Our empirical study demonstrates that households where men retired first had a much lower satisfaction than households where women retired first. In addition, men were found to show lower satisfaction than wives in both households where women retire first and the households where men retire first. Retirement sequence affecting their satisfaction at the point when only one of the spouses is retired continues to affect their satisfaction after both of them are retired. This means that the difference in the couple's retirement sequence has an ongoing effect on their later happiness. The analysis of the effect of a couple's retirement sequence on the satisfaction in their old life may be useful for improving an individual and couples' quality of life in countries with similar cultures.